(untitled) (African Journal of Law and Politics, 2023)
Violence against men is rampant today and is a serious disease that eats up the society. The study investigates violence against men as seen by the population of Bamenda in five recognised institutions in Cameroon. The researcher constructed a questionnaire which was used for data collection. Data collected was analysed using Statistical Package for the Social Sciences Version 20 Excel 2016 and Microsoft word 2016. The findings revealed that men suffered from various forms of violence in Bamenda ranging from psychological to emotional violence. This is because when a man is not mentally balance, it leads to serious trauma, stress and depression. However, men faced some challenges such as lack of male empowerment centres, manifestations of masculinity to prove that they do not experience violence, men do not report any case of violence against them etc. Thus, based on the findings, some recommendations have been made for the legislator should draft and adopt the polygamous code, the government should put in place a psycho-social centre where men going through psychological trauma can be counselled, etc.